2015
DOI: 10.7863/ultra.34.5.907
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐Enhanced Sonographically Guided Thermal Ablation for Treatment of Solid‐Organ Hemorrhage

Abstract: The purpose of this series was to preliminarily evaluate the use of contrast‐enhanced sonographically guided percutaneous thermal ablation in the evaluation and treatment of solid‐organ bleeding by retrospectively analyzing 6 cases observed in clinical practice. Six patients who underwent contrast‐enhanced sonographically guided thermal ablation for treatment of solid‐organ bleeding (5 in liver and 1 in spleen) from December 2005 to August 2012 were included in this series. Clinical information, contrast‐enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A total of 12 studies (all case series) fall into this miscellaneous section, which includes 4 categories of CEUS assisted procedures: (1) US‐guided abscess drainage; (2) US‐guided percutaneous nephrostomy; (3) US‐guided biliary interventions; and (4) hepatic and splenic hemorrhage. In the first 3 categories, a diluted contrast solution (ie, 0.1 mL of SonoVue in 20 mL of saline) is injected directly in the catheter or needle to visualize the exact location of the cavity or tissue around the catheter or needle tip: so‐called intracavitary CEUS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 12 studies (all case series) fall into this miscellaneous section, which includes 4 categories of CEUS assisted procedures: (1) US‐guided abscess drainage; (2) US‐guided percutaneous nephrostomy; (3) US‐guided biliary interventions; and (4) hepatic and splenic hemorrhage. In the first 3 categories, a diluted contrast solution (ie, 0.1 mL of SonoVue in 20 mL of saline) is injected directly in the catheter or needle to visualize the exact location of the cavity or tissue around the catheter or needle tip: so‐called intracavitary CEUS.…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous use of CEUS to detect and guide percutaneous treatment of splenic and hepatic hemorrhage or lesions after trauma or biopsy has been reported in 4 series, but only in 2 series was another imaging technique (CT) used as the reference standard, which resulted in a detection rate of 100% in both . Three of the studies reported on CEUS‐guided percutaneous treatment of hemorrhage . In 1 study, bleeding successfully resolved with thermal ablation in 4 of 5 cases .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the currently used imaging methods, ultrasound is relatively more suitable for examination during ablation, and studies have shown that CEUS is sensitive to detect trauma-caused bleeding in solid organs with a similar accuracy as enhanced computerised tomography [30,31]. Thus, CEUS is effective for detecting needle tract bleeding during ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasound and diagnostic peritoneal lavage have high sensitivity in the detection of complications of abdominal injuries, the diagnostic methods have low value in the absence of the free flow of fluid. Even a CT scan has low sensitivity in detecting abdominal injuries, including mesentery, intestines, pancreas, and diaphragm injuries ( 22 24 ). In addition, emergency physicians do not have clear criteria for early discharge of patients with blunt abdominal trauma before using a CT scan ( 25 ).…”
Section: Introductionmentioning
confidence: 99%